Giant intrinsic photoresponse in pristine graphene - Ma, Qiong (2020)
When the Fermi level is aligned with the Dirac point of graphene, reduced charge screening greatly enhances electron-electron scattering1-5. In an optically excited system, the kinematics of electron-electron scattering in Dirac fermions is predicted to give rise to novel optoelectronic phenomena6-11. In this paper, we report on the observation of an intrinsic photocurrent in graphene, which occurs in a different parameter regime from all the previously observed photothermoelectric or photovoltaic photocurrents in graphene12-20: the photocurrent emerges exclusively at the charge neutrality point, requiring no finite doping. Unlike other photocurrent types that are enhanced near p-n or contact junctions, the photocurrent observed in our work arises near the edges/corners. By systematic data analyses, we show that the phenomenon stems from the unique electron-electron scattering kinematics in charge-neutral graphene. Our results not only highlight the intriguing electron dynamics in the optoelectronic response of Dirac fermions, but also offer a new scheme for photodetection and energy harvesting applications based on intrinsic, charge-neutral Dirac fermions.